Biomechanical Evaluation of Strength and Stiffness of Subtalar Joint Arthrodesis Screw Constructs. (April 2016) - Jastifer, James R.; Alrafeek, Saif; Howard, Peter; Gustafson, Peter A.; Coughlin, Michael J.
Background: Subtalar arthrodesis is a common treatment for end-stage subtalar joint arthritis as well as many other clinical problems. The best method of subtalar arthrodesis fixation is unknown. The purpose of this study was to compare the strength of subtalar arthrodesis fixation methods including a single posterior screw (SP), 2 posterior minimally divergent screws (MD) and a 2 screw highly divergent screw (HD) construct for subtalar arthrodesis. Methods: A biomechanical study was performed including the three different screw configurations (SP, MD, HD). These surrogate bone specimens were subjected to applied inversion and eversion torques about the subtalar joint axis on a servo-hydraulic load frame. Torsional stiffness of the construct and the maximum torque for each configuration were measured. Additionally, a cadaver study was performed using 5 fresh-frozen cadaver specimens. The perpendicular distance from the divergent screw guide-wire placement was measured from anatomic structures. Results: The HD screw configuration was found to have the highest torsional stiffness in both inversion and eversion, followed by the MD construct and then the SP construct. Similarly, the HD construct had the highest maximum torque versus the MD and SP constructs. All between-group differences were statistically significant ( P < .05). The mean distance from key structures to the divergent screw included the sural nerve (13 mm), peroneus brevis tendon (18 mm), tibialis anterior tendon (8 mm), and tibialis posterior tendon (21 mm). Conclusion: This biomechanical and cadaver study supports the use of 2 screws for fixation of subtalar arthrodesis over a single posterior screw. Additionally, we describe a biomechanically superior and potentially safe, alternative 2-screw divergent construct. Clinical Relevance: This study gives biomechanical support for 2 screw, divergent fixation of subtalar arthrodesis or a single over a single screw or two screw minimally divergent construct.